Minimizing the Energy Cost of Servers in Data Center Networks - Jun Wu; Qin Jia; Jin Zhao; Xin Wang (2012 International Conference on Cloud and Green Computing, 2012)
To alleviate the growing concern of energy waste in networked devices, we propose an energy saving strategy in the "server-centric" data center network. Focusing on servers, we introduce a basic scheme based on the transition of automata. By changing efficiently from sleeping state to active state in different network traffic, servers save the energy. This scheme is self-adaptive and simple. Based on this prime scheme, we enhance the strategy by further taking advantage of the unique topology of BCube. We present a structure algorithm relying on the active substructure in BCube. Combining with the basic scheme and structure algorithm, our energy saving strategy can achieve a high proportion of energy saving without sacrificing service quality like packet delay in the simulation with real traffic trace.